Global restructuring and resistance in an age of austerity: a critical political economy of the Eurozone crisis in Greece and Portugal - Jordan, Jamie (2017)
This thesis analyses the political economic origins of, and responses to, the eurozone crisis in Greece and Portugal. Part 1 develops a Critical Political Economy (CPE) approach to studying the economic development of European capitalism(s). The development of this CPE approach takes place through a critical engagement with authors employing a Varieties of Capitalism Approach (VoC). This critique is considered important as the VoC approach offers an institutionalist theory of capitalist diversity. Instead, what is required when explaining trajectories of development, change and contestation across European varieties of capitalism is a capitalist theory of institutional diversity. In other words, whilst varieties of capitalism do evidently exist, the institutional diversity they exhibit (whether it be path-dependent or transformed) is always and already embedded as varieties in capitalism. This has to be taken seriously to adequately explain the systemic origins of, and responses to, the eurozone crisis in Greece and Portugal.